Response of Small Diameter Steel Piles in Sand Under Lateral Load - Mujah, Donovan; Ahmad, F.; Hazarika, H.; Watanabe, N. (International Geosynthetics Society (IGS) Thailand Chapter, 2012)
Conventionally, passive piles are used in resisting lateral movement of soil mass in landslide prevention measure. Such piles are installed vertically in a row, so that pile resistance is generated through the shearing between the embedded pile lengths with slope surface. While cast in-situ concrete piles with diameter up to 1 m are still widely used in practice, a new type of pile called the small diameter steel piles (SDSP) has been developed recently as alternative. With diameter spanning only between 90 mm to 300 mm, SDSP is expected to function as both preventive piles as well as reinforcing rod in landslide prone slopes. This paper intends to shade light on the prevention mechanism of small diameter steel piles (SDSP) and how multirow arrangement of piles affects the reinforced slope failure in landslide prevention. To that end, laboratory scale experiment using direct shear test was performed to replicate the lateral soil movement induced by landslide in which, Toyoura sand and aluminum rods were used to simulate ground condition and steel piles respectively. Likewise, finite element analysis (FEA) employing Mohr-Coulomb’s elastic-perfectly plastic soil model was also carried out to simulate the experiment. In this study, the effect of the ground density and cross sections of reinforcing rods in piles’ prevention mechanism were considered. Based on the results, it was found that the failure mode of dense ground is governed by soil’s shearing resistance mobilized at a higher strain, while bending stiffness of the reinforcing material is more dominant in loose ground regardless of the piles arrangements.